The Effect of Number Gema Application on the Ability to Recognize Number Concepts in Children Aged 5-6 Years at Kindergarten Negeri Pembina 1 Pekanbaru - Meilisa, Sarah; Kurnia, Rita; Tambunan, Novidawaty (Journal of English Language and Education, 2025)
Early childhood is a golden period of child development, including cognitive aspects such as the ability to recognize the concept of numbers. This study aims to determine the influence of the Gema Numbers application on the ability to recognize numbers of children aged 5-6 years in Kindergarten Negeri Pembina 1 Pekanbaru City. The method used was an experiment with the One Group Pre-test Post-test design. A total of 20 children participated in learning using the application for four meetings. The pretest results showed that the child's ability was still low (40.5%), while the posttest results increased significantly to 83.5%. All indicators of number ability have increased, from recognizing symbols to comparing numbers. The results of the t-test showed a significant influence of the use of the app on improving children's abilities. Thus, the Gema Numbers application is effectively used as a fun interactive learning medium in introducing the concept of numbers to early childhood.